Advokasi Pengelolaan dan Layanan PAUD Berkualitas di Kota Samarinda - Sjamsir, Hasbi; Liana, Heppy; Aslinda, Andi; Bulan, Syahri (TAAWUN, 2022)
This community service activity aims to advocate for Quality ECD Management and Services in Samarinda City. Furthermore, through this PKM activity PAUD educators are expected to understand that quality PAUD is determined by the quality of services, the quality of the learning process and the quality of management of PAUD units (PP SNP no. 57 of 2021). In other words, quality ECD is an integral part of holistic integrative learning services so that they can implement more effective learning in developing aspects and skills of AUD development in ECD units as well as motivating children to be more enthusiastic in learning activities. Therefore. It must be understood that educators and education personnel are the foundation of quality ECD. The capacity and welfare of PTK needs to be a concern so that the four elements of quality PAUD can be realized. The methods used in this PKM consist of various methods, namely lectures, active discussions, FGDs, DARING and simulations on the application of LURING Quality ECD Management and Services. The level of understanding of the concept of the Four Elements of service program in PAUD is quite adequate as seen when given a kind of summative test, and the average participant gets a score of 78 on a scale of 100. In the future, it is still necessary to monitor the application of these Quality ECD Management and Service to make this PKM activity more effective.